2020
DOI: 10.3892/or.2020.7522
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA TPTEP1 competitively sponges miR‑328‑5p to inhibit the proliferation of non‑small cell lung cancer cells

Abstract: Accumulating evidence suggests that lncRNAs are involved in almost all normal physiological processes and that aberrant expression of lncRNAs may be involved in the development of diseases, including non-small cell lung cancer (NSCLC). However, the roles of lncRNA-TPTE pseudogene 1 (TPTEP1) in lung cancer and the underlying molecular mechanisms have remained elusive. In the present study, significant downregulation of TPTEP1 in tumors compared with normal tissues from patients with NSCLC was observed. Overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
0
19
1
Order By: Relevance
“…The results of the present study confirmed that mirna-106a-5p serves as an oncogene by augmenting TPTeP1-mediated stemness and radioresistance of glioma. Previous studies have demonstrated the stimulating effects of TPTeP1 and the inhibitory effect of mirna-106a-5p on cancer cell apoptosis (33,35,43). Thus, prospective studies will aim to elucidate the effect of TPTeP1 and mir-106-5p on glioma cell apoptosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the present study confirmed that mirna-106a-5p serves as an oncogene by augmenting TPTeP1-mediated stemness and radioresistance of glioma. Previous studies have demonstrated the stimulating effects of TPTeP1 and the inhibitory effect of mirna-106a-5p on cancer cell apoptosis (33,35,43). Thus, prospective studies will aim to elucidate the effect of TPTeP1 and mir-106-5p on glioma cell apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…TPTeP1 acts as a tumor suppressor in hepatocellular carcinoma (33,34) and lung cancer (35), and has been reported to participate in the modulation of several biological functions, including cell proliferation, invasion, chemoresistance and inflammation (33)(34)(35) . In addition, bioinformatic analysis suggests that TPTeP1 may serve as a tumor suppressor in the development of GBM (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several aberrantly expressed lncRNAs have been found associated with B–ALL [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. For instance, Fernando et al [ 19 ] highlighted the over–expression of the lncRNA CASC15 with regulatory roles on the transcriptional factor SOX4, in paediatric RUNX–1 translocated B–ALL.…”
Section: Introductionmentioning
confidence: 99%
“…As reported before, various lncRNAs can regulate cell proliferation and migration. For instance, lncRNA TPTEP1 could inhibit the non-small cell lung cancer (NSCLC) cells to proliferate through abating miR-328-5p expression (Cao et al, 2020). In addition, in renal cell carcinoma, lncRNA00312 attenuated cell proliferation and migration obviously (Zeng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%